Hungarian Monitoring, 16 July 1988 . [Magyar rádiófigyelő], 1988. július 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Western reception of Gorbachev's Warsaw Pact recommendations - Tension in Karabakh hill region Domestic Affairs: - Károly Grósz statement on Warsaw Pact body meeting and Party renovation - Rezső Nyers statement on political and economic questions - Gabčíkovo-Nagymaros dam affair and the Danube movement - National minorities in Transcarpathia - Works by Kundera and Solzhenitsyn published Külpolitika - Gorbacsov VSZ javaslatainak nyugati visszhangja - Feszültség a Karabah-hegyvidéken Belpolitika - Grósz Károly nyilatkozik a VSZ testületi üléséről és a párt megújításáról - Nyers Rezső nyilatkozik politikai és gazdasági kérdésekről - A bős - Nagymarosi vízlépcső ügye és a Duna-mozgalom - Nemzetiségek helyzete Kárpátalján - Kundera és Szolzsenyicin művek megjelenése